2018
DOI: 10.1016/j.jgo.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of older African-American and Non-Hispanic white breast cancer survivors from diverse socioeconomic backgrounds toward physical activity: A qualitative study

Abstract: Among older BCS, physical activity preferences were shaped by cancer experience, rather than by race and SES. Physical activity programs for older BCS should focus on addressing cancer treatment-related concerns and should include strength training to ensure PA programs are more acceptable to older BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…Resistance weight and strength training were also commonly reported PA types. In their qualitative and quantitative studies, Owusu et al [ 54 ] and Rogers et al [ 55 ] found that half of breast cancer patient participants preferred resistance weight and strength training during the treatment and post-treatment stages. Other PA type preferences reported by patients across cancer types included gardening, jogging, ball sports, dancing, gymnastics and stretching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance weight and strength training were also commonly reported PA types. In their qualitative and quantitative studies, Owusu et al [ 54 ] and Rogers et al [ 55 ] found that half of breast cancer patient participants preferred resistance weight and strength training during the treatment and post-treatment stages. Other PA type preferences reported by patients across cancer types included gardening, jogging, ball sports, dancing, gymnastics and stretching.…”
Section: Resultsmentioning
confidence: 99%
“…Companionship was a common facilitator reported by patients across cancer types. In their qualitative and quantitative studies, Owusu et al [ 54 ] and Mizrahi et al [ 71 ] found that group exercising with significant others and/or other cancer patients who face similar challenges was a major facilitator among 80–95% of the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Older breast cancer survivors mentioned that an active lifestyle help to reduce the stress levels and combat depression. 17 At the same time, Mazzoni et al 28 found that patients exercising during oncological treatments reported a feeling of self-control.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by Engel's critique of the biomedical approach to illness [32] and in line with contemporary health-behaviour models [33,34], it could be argued that a multi-perspective understanding of PA behaviour in long-term BC survivorship, including both qualitative and quantitative dimensions of PA, could direct greater attention to the specific challenges of all sub-groups of BCSs. Hence, knowing that lack of time, in combination with fatigue, is a pronounced challenge among BCSs [7,11], and that time scarcity may be related to social health inequalities [35], approaches depicting BCSs' time-use might allow important, but previously overlooked, aspects of these variables to surface.…”
Section: Introductionmentioning
confidence: 99%